33‐2: Invited Paper: Flexible OLED Displays with Ink‐Jet Printing Technology. Issue 1 (28th June 2022) - Cao, Weiran; Li, Jinchuan; Li, Xiang-Long; Liu, Yunxi; Hsu, Yuan-Jun; Wu, Yuan-Chun; Zhang, Xin; Yan, Xiaolin
Abstract : TCL CSOT has been investing in ink‐jet printing AMOLED technology for many years, and now CSOT has mastered the complete manufacturing process for IJP display technology, including rigid and flexible technology to manufacture middle and large size OLED displays. Flexible technologies such as panel design, substrate, TFT backplane, EL device, thin film encapsulation, module, and compensation have been developed. Attractive flexible prototypes including 14~31‐inch OLED have been demonstrated in the past three years. TCL CSOT expects to provide innovative flexible OLED displays in the near future.